2018
DOI: 10.1177/2516865718813122
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices of Women Toward Prenatal Genetic Testing

Abstract: Objectives:We aim to address public knowledge, attitudes, and practices relative to prenatal genetic testing as a starting point for policy development in Jordan.Study design:We conducted a cross-sectional prenatal genetic testing knowledge, attitudes, and practices survey with 1111 women recruited at obstetrics and gynecology clinics nationwide. Data were analyzed using a variety of descriptive and inferential statistical tests.Results:The overwhelming majority (>94%) of participants considered prenatal genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 41 publications
(113 reference statements)
2
14
1
Order By: Relevance
“…In this study, the a tude of the high-risk pregnant women following counselling was unfavorable towards the prenatal invasive tests despite the fact that majority of the pregnant women were from urban area with higher educa on and in the age group of 21-30 years. Similar demographic profiles 10 were observed in the studies done by Tsai GJ, et al where 48% of women were below the age of 30 years and by Graaf IM De et al where around 80% of the women were from the 11,14,15 urban residence. It is also important to note that post counselling; both women and husbands had unfavorable a tude towards the prenatal invasive tests in spite of the repor ng that their knowledge and understanding was adequate and both of them were mature enough to make the decisions on their own.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, the a tude of the high-risk pregnant women following counselling was unfavorable towards the prenatal invasive tests despite the fact that majority of the pregnant women were from urban area with higher educa on and in the age group of 21-30 years. Similar demographic profiles 10 were observed in the studies done by Tsai GJ, et al where 48% of women were below the age of 30 years and by Graaf IM De et al where around 80% of the women were from the 11,14,15 urban residence. It is also important to note that post counselling; both women and husbands had unfavorable a tude towards the prenatal invasive tests in spite of the repor ng that their knowledge and understanding was adequate and both of them were mature enough to make the decisions on their own.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies reported a deficiency of knowledge of genetic testing among the public, including populations in developed and developing nations (Vermeulen et al, 2014 ; Agurs-Collins et al, 2015 ; Hann et al, 2017 ; Eum et al, 2018 ; Altaany et al, 2019 ). Meanwhile, similar studies targeting prenatal or neonatal genetic testing revealed that health education, facilities, and infrastructures should be further improved to enhance the adaptation of non-invasive genetic testing among the public (Kusyk et al, 2013 ; Abdo et al, 2018 ). Moreover, Colotto et al ( 2015 ) reported a good level of awareness of and interest in genetic testing among medical students (Colotto et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, In Rumania, Pop-Tudose et al (2018), found that 48% of women have never have heard about any test for Down's syndrome detection. Differently to this Abdo et al (2018), found that more than 94% of Jordanian women would consider having a prenatal testing, specially cfDNA testing, although this rate was lower in women with less education.…”
Section: Comparison With the Literaturementioning
confidence: 80%